Atypical presentation of type B aortic dissection mimicking appendicitis managed medically. (29th June 2018) - Azharuddin, Muhammad; Delacruz, Maria Amanda; Baughman, Derek; Chandler, Patton
Abstract : This is a case of a 53-year-old male patient with a history of hypertension who developed sudden onset of right lower quadrant pain. On arrival, chest X-ray showed prominent aortic arch without cardiomegaly. CT of the abdomen/pelvis showed aortic dissection in descending aorta without rupture. CT of the chest displayed sparing of ascending and aortic arch. Ultrasound Doppler of the kidney displayed mild renal artery stenosis. Differential diagnosis was acute appendicitis, acute ureteric and severe gastroenteritis. The patient was started on oral blood pressure (BP) medicine to titrate off intravenous nicardipine and esmolol drip. After 10 days, he was switched to oral BP medicine. His leg pain was resolved with normal palpable pulse. One week later, his kidney function worsened. Thus, Lasix and minoxidil were stopped. The patient had no chest/abdominal pain and was tolerating the medicine well during his 2-week follow-up. Acute aortic dissection can be a fatal clinical emergency. Timing is critical during diagnosis and management of patients.